Distribution of Xantusia extorris at the state of Coahuila, Mexico, with comments on its natural history - Castañeda-Gaytán, J. Gamaliel; Castañeda-Gaytán, J.J.; Cano-Villegas, O.; García-Vázquez, U. O. (Instituto de Ecología, A.C., 2013)
-